Fire in the Wildland-Urban Interface: Selecting and Maintaining Firewise Plants for Landscaping - Raelene Crandall; Jennifer Fill; Alan Long; Cotton Randall; Douglas Doran (EDIS)
For homeowners who live in an area with a medium to high risk of wildfire, creating an area of defensible space is crucial for protecting homes. The movement of a wildfire is controlled primarily by the flammability of the plants present and how those plants are arranged, both vertically and horizontally. This publication details how the structure and composition of the vegetation, from leaf to the whole plant, affect the likelihood that a fire will ignite and spread. It also describes how plants' horizontal and vertical arrangement can affect wildfire ignition and spread near homes, concluding with recommendations for firewise landscaping.